Effective detection of ZnO in nicotine using butterfly wing scales - Thanachai Changcharoen; Thidsanu Apiphatnaphakul; Wasupon Watjanavarreerat; Kitsakorn Locharoenrat (Artificial Cells Nanomedicine and Biotechnology, 2022)
without aggregation. This photonic sensor is an alternative to the present-day methods for the rapid test of ZnO content, which is very simple without complicated instrumentation. Furthermore, our method might become a starting point for the advancement of portable instruments for onsite ZnO detection.
Keywords: Neurobiology and Insect Physiology Research; Physiological and biochemical adaptations